Potential Value of Acridids as High Protein Supplement for Poultry Feed - Anand, Hena; Ganguly, Arijit; Haldar, Parimalendu (International Journal of Poultry Science, 2008)
It is well known that acridids are an attractive and important natural source of food for many kinds of vertebrate animals, including birds, lizards, snakes, amphibians, fish and other mammals. Despite that they drew very few research attentions as feed for domesticated animals, particularly poultry, swine and freshwater fish. In the present study energy estimation and proximate analysis were conducted for four acridid species in order to determine the nutritional quality of those species and their potential value as an alternative animal protein source. The experiment revealed acridids to have a higher amount of protein content in compared to the conventional soybean and fish meals. A high amount of caloric contents were also evident in the chosen acridids. The most important conclusion of this study was that the acridids can provide a reliable and sustainable source of high quality animal protein for domesticated animals.